Siringomielia por malformación de Chiari: resolución espontánea. Revisión bibliográfica - Mezzadri, Juan Jose (Revista Argentina de Neurocirugía, 2021)
Abstract: The aim of this review is to describe cases of syringomyelia caused by Chiari type 1 malformation with spontaneous resolution, analyze its causes and therapeutic implications. In the adult population there were 22 cases (medium age: 35.81) and in the pediatric population there were 37 cases (medium age: 9.82). The hypothesis about the mechanisms that produce the spontaneous resolution were: changes in tonsils position related to age, cerebellar atrophy, cord fissures, reduction of physical effort, variations in intraspinal pressure, skull growth and decrease in intracranial pressure. The spontaneous resolution of syringomyelia invites to carry out regular check-ups and avoid surgery. However, waiting carries risks with the possibility of acute worsening or permanent sequelae. The information available today does not allow to predict with certainty the evolution of each case.
Keywords: Chiari malformation – spontaneous resolution – syringomyelia